Sifat Nilai Eigen Matriks Antiadjacency dari Graf Simetrik - Noni selvia (LPPM, 2017)
Antiadjacency matrix is one of the ways to represent a directed graph . Let G be a directed graph with V(G)=v1, v2, . . ., vn . The adjacency matrix of G is a matrix A=(aij) of order n x n , with aij=1 if there is an edge from vi to vj , for i not equal j , otherwise aij will equals 0. The matrix B= J - A is called the antiadjacency matrix of G, with J is a matrix of order n x n with all entries equal to 1. In this paper, it will show characteristic of eigenvalue of antiadjacency matrix of symmetric graph. Keywords : antiadjacency matrix, a symmetric graph, characteristic of eigenvalue